Depressive symptoms and suicidal ideation in sexual minority adolescents: An examination of social reward responsiveness and support as moderators - Yinru Long; Samantha Pegg; Christian A.L. Bean; Andrew Kittleson; Kirsty Clark; Autumn Kujawa (Journal of Mood and Anxiety Disorders)
Sexual minority (SM) youth are at increased risk of depression and suicidal ideation (SI), due in part to discrimination and other stressors. This raises questions about social factors that may increase risk or resilience to stressors commonly faced by SM youth. The goal of this multimethod study was to examine both neural processing of social feedback and perceived social support as potential moderators of the association between SM identity, depressive symptoms, and endorsement of SI in adolescents. For this study, 165 adolescents aged 14–17 (22.42 % identifying as SM) were oversampled for current depression. Participants self-reported social support, depressive symptoms, and SI. Electroencephalogram (EEG) was recorded while participants completed a computerized peer interaction task in which the reward positivity (RewP) component was measured in response to social acceptance vs. rejection feedback. We tested social RewP and social support as moderators of associations between SM identity, depressive symptoms, and whether SI was reported. SM youth reported lower social support and elevated depressive symptoms and were more likely to endorse SI compared to non-SM youth. Social RewP moderated the associations between SM identity, depressive symptoms, and SI such that SM youth with blunted neural responses to social acceptance had higher depression and were more likely to endorse SI. Lower social support was associated with greater depressive symptoms and SI, but social support was not a significant moderator of the association between SM identity and symptoms. This is among the first studies to use affective neuroscience methods to examine social processes in SGM youth and our findings underscore the role of social factors in SGM youth mental health.